Implementation of Entrepreneurship Orientation to Improve SME Performance - Rusandy, Deby Santyo (Universitas Dharma Wacana, 2024)
Micro, small, and medium firms from both the traditional and contemporary sectors make up the vast majority of Indonesia's labour force, making SMEs among the most significant economic actors in the country. Improving the efficiency of small and medium-sized woven fabric businesses in Lombok is the primary goal of this research. In this study, an explanatory approach was used. The purpose of this research was to examine potential causal explanations for observed patterns. The study's findings Small and medium-sized enterprises (SMEs) producing woven fabrics in Lombok have benefited greatly from an entrepreneurial mindset in the last three years. Small and medium-sized enterprises (SMEs) producing woven fabrics in Lombok are heavily affected by their working conditions. For woven fabric SMEs in Lombok, a positive result for the route coefficient between the workplace and performance indicates a unidirectional link or effect. In today's friendly business environment, entrepreneurial orientation influences performance, and future business environment conditions are not always predictable. It is necessary to anticipate some alternative problem-solving, so entrepreneurial orientation that theoretically affects performance must be formulated to achieve goals and implement strategies effectively. Since previous studies have shown that the impact of entrepreneurial orientation on business performance is inconsistent, such as through the use of social media and E-commerce, it is important to conduct additional research on the environmental impact on performance improvement in the context of Lombok's small and medium-sized enterprises (SMEs) that produce woven fabrics.